Challenges in data representation for efficient execution of encryption operation - Afendee Mohamed, Mohamad; Garba Shawai, Yahaya; Almaiah, Mohammed Amin; Derahman, Mohd Noor; Lutfi, Abdalwali; Abu Bakar, Khairul Azmi (Bulletin of Electrical Engineering and Informatics, 2024)
Big number operation has always been a bottleneck to computer system as it imposes high demand on computing power. With a limited power available, operations such as exponentiation and multiplication involving large integer belonging to encryption process requires grave scrutiny. One way to address this issue is by replacing an original complex computation into a sequence of small computations that in the end produces the same results. This paper takes an evolutionary approach to survey numerous articles that have contributed to the advancement of integer representation. Numerous representations were proposed, those that come into play concentrated on reducing non-zero digits and limiting non-zero spacing other than allowing subtraction operation. A comparison was made to distinguish the properties of each method from the others. This detailed outlook can be a guide for identifying the correct representation to be chosen for implementation within specific application.